Ecofriendly development of electrospun antibacterial membranes loaded with silver nanoparticles. Issue 2 (June 2022) - Irfan, Muhammad; Uddin, Zia; Ahmad, Faheem; Rasheed, Abher; Qadir, Muhammad Bilal; Ahmad, Sheraz; Aykut, Yakup; Nazir, Ahsan
Functional polymeric membranes with antibacterial properties have gained significant importance in many applications. Silver NPs offer advantage over other materials for their effective antibacterial properties and being safer for humans at low concentrations. The synthesis of silver NPs may not always be environmental friendly and their incorporation in the polymer membranes is usually a multistep process. In this study, PVDF/PVP/AgNPs electrospun membranes were developed in a single step process where silver NPs were synthesized using reducing and stabilizing properties of PVP. The UV-vis spectroscopy confirmed the synthesis of silver NPs in PVP solution by sharp absorption peak at 398 nm. The membranes were loaded with various concentrations of silver NPs (1, 1.5, 2 and 2.5 wt%). The scanning electron microscopy of the developed membranes showed nano fibers of uniform diameter at optimized electrospinning conditions. FTIR spectroscopy also confirmed the successful development of polymeric composite (PVDF/PVP/AgNPs) membranes. The composite membranes demonstrated effective antibacterial properties against Staphylococcus aureus in disk diffusion test. The size of the inhibition halo increased with the concentration of the silver NPs in electrospun membranes. The findings of this study will be helpful in the simple and environmentally friendly development of antibacterial membranes for applications such as air and water filtration.